Enteromorpha maeotica pr.-lavr. (chlorophyta) dans le complexe lagunaire Sinoe - Vasiliu, Florian; Stadniciuc, Maria (Cercetări Marine - Recherches Marines, 2026)
This paper deals with Enteromorpha maeotica PR.-LAVR. (Chlorophyta) presence in the Sinoe Lake along the Romanian Black Sea shore.